A STUDY OF EIGHTH GRADE STUDENTS AT SMP NEGERI 4 KOTA BENGKULU: STUDENTS' MASTERY IN DEGREES OF COMPARISON - Kinanti, Salzabilla Ayu; Zahrida; Kurniawan, Ildi (UNIB Press, 2025)
The purpose of this study was to find out the ability of students in grade VIII of SMP Negeri 4 Kota Bengkulu in mastering the degrees of comparison material. This research is case study and using a quantitative descriptive method. The subjects in this study were 64 students of class VIII which were divided into 2 classes, namely class 86 which amounted to 33 students, and class 87 which amounted to 31 students. The instruments used in this research are test which are the main instrument and interview as an additional instrument. The test given to students was 30 items with 3 different types of questions. In analyzing the data, researcher used several formulas. The results showed that students of grade VIII SMP Negeri 4 Kota Bengkulu in the in academic year 2022/2023 were able to use degrees of comparison with a percentage of ability of 68.2%, and the level of student ability was categorized into fair. The problems faced by students of grade VIII SMP Negeri 4 Kota Bengkulu in the academic year 2022/2023 are in the material of degrees of comparison, namely their lack of understanding in using more or most and -er or -est on adjectives and irregular adjective.